Salinity Effects on Microbial Derived-C of Coastal Wetland Soils in the Yellow River Delta - Shao, Pengshuai; Han, Hongyan; Sun, Jingkuan; Yang, Hongjun; Xie, Hongtu (Frontiers in Ecology and Evolution, 2022)
Microorganisms play the crucial role in regulating the turnover and transformation of soil organic carbon (SOC), whereas microbial contribution to SOC formation and storage is still unclear in coastal wetlands. In this study, we collected topsoil (0-20 cm) with 7 salinity concentrations, and explored the shifts in microbial residues (represented by amino sugar) and their contribution to SOC pool of coastal wetlands in the Yellow River delta. The gradually increasing soil salinity reduced soil water content, SOC, and soil nitrogen (N), especially in high salinity soils of coastal wetlands. Total amino sugars and its ratio to SOC respectively decreased by 90.56% and 66.35% from low salinity to high salinity soils, indicating that coastal wetlands with high salinity restrained microbial residues accumulation and microbial residue-C retention in SOC pool. Together with redundancy analysis and path analysis, we found that soil water content, pH, SOC, soil N, and glucosamine/muramic arid were positively associated with the ratio of amino sugars to SOC. The higher available soil resource (i.e., water, C substrate and nutrient) increased microbial residues accumulation, promoting microbial derived-C contribution to SOC in low salinity coastal wetlands. The greatly deceased microbial residues contribution to SOC might be ascribed to microbial stress strategy and low available C substrate in coastal wetlands with high salinity concentration. Additionally, the gradually increasing salinity reduced fungal residues contribution to SOC, but did not change bacterial residues contribution to SOC. These findings indicated that changed fungal residues would substantially influence SOC storage. Our study elucidates microbial contribution to SOC pool through residues reservoir in coastal wetlands, and push microbial metabolites to a new application in global wetland SOC cycling.